1988
DOI: 10.1002/pssb.2221460109
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition and Anharmonic Properties of Semimagnetic Semiconductors

Abstract: The phase transition and anharmonic properties are investigated of semimagnetic semiconductors Cdl-&,Te and Cdl-,Zn,Te using a three-body force potential. The calculated values of third order elastic constants follow a systematic trend of variation with molar concentration. The values of the phase transition pressures and the pressure derivatives of second order elastic constants show reasonably good agreement with their experimental data. The possible ways of improvements are also discussed.Der Phasenubergang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The Complete lattice dynamical, thermodynamical property and density of state curve of MgOtheoretically reported has agreed with different reported data [15][16][17][18][19][20][21][22][23][24][25][26]. The authors and more researchers have already used the present model and successfully reported the value of alkali halides and semiconductor materials [31][32][33][34][35][36][37].To sum up, we can say that the contributions of VWI and TBI are essential for the description of the lattice dynamics and thermodynamical study of MgO.…”
Section: Discussionsupporting
confidence: 87%
“…The Complete lattice dynamical, thermodynamical property and density of state curve of MgOtheoretically reported has agreed with different reported data [15][16][17][18][19][20][21][22][23][24][25][26]. The authors and more researchers have already used the present model and successfully reported the value of alkali halides and semiconductor materials [31][32][33][34][35][36][37].To sum up, we can say that the contributions of VWI and TBI are essential for the description of the lattice dynamics and thermodynamical study of MgO.…”
Section: Discussionsupporting
confidence: 87%
“…Looking to the good description of elastic properties, we have extended our investigation to the determination of anharmonic properties, namely the TOEC and pressure derivatives of SOEC such as dB/dP, dS/dP and dC 44 /dP using the expression given in Ref. [12]. The results are given in Tables 4 and 5.…”
Section: Resultsmentioning
confidence: 99%
“…The details of the three-body interaction potential and method of calculation adopted in the present paper are presented elsewhere [12,13]. Here, we briefly outline some of the useful features of the three-body interaction potential.…”
Section: Theory and Methods Of Calculationmentioning
confidence: 99%
See 2 more Smart Citations